Processos educativos estéticos vivenciados através do cinema por participantes de um Centro de Atenção Psicossocial álcool e drogas - Gotler, Sônia (2016)
In eight weekly meetings that took place in a municipality in the north of the State of Rio Grande do Sul , this study looked at the esthetic educational processes experienced through movies by a group of subjects comprising 40 men and 6 women who are problematic users of psychoactive substances and utilize the services of a Center for Psychosocial Care for Alcohol and Drugs-CAPSad and two professionals belonging to the team that treats these people. The general objective of the study was to investigate the significance of esthetic-educational processes experienced by the participants through the movies. The specific objectives were to observe, describe, understand and interpret these processes through movies selected especially for this group.. The subjects already gathered weekly to watch movies, at that service, under the coordination of a professional from the team. The study was qualitative of a phenomenological nature. The tools to collect information were the field diary and the free group interview (participatory research tool), taped and then transcribed. The first two meetings were to approach the people who were the subjects of the study, and thus, select the movies with their collaboration. From the third to the eighth meeting the purpose was to watch the films and then hold a Cineforum according to the model of Guerra (1998). The guiding questions of the discussion were: “What did the film means to you? What does the film say about you?” In order to organize and understand the information, the four-step phenomenological method was used, proposed by Giorgi (2009) and a fifth by Comiotto (1992). Namely: the sense of the whole; the units of significance; the transformation of the significant units into psychoeducational language; synthesis of the structures of meaning; phenomenological dimensions. Five essences (called images )arose with with three dimensions (called impressions) each, respectively: TERRITORY AND BORDERS: CAPSad is a territory; stigma, prejudice and resilience; borders between fiction and reality. MOVIES: THE THEATER OF THE SKIN: amusement, humor and self-distancing; charm and perception of beauty; the Devil as an ally: pleasure and pain; BECOMING ONESELF: the look of the other; the spectator as creator; liberty and destiny. THE MOVIE THAT MAKES ONE THINK: movies that made one think; movies as a cultural practice; movies and education. PSYCHOACTIVE SUBSTANCES: USES AND ABUSES: legalization; reduction of damage and medicinal use; light and heavy drugs; sensitivity and anesthesia.. This investigation provided knowledge and sought theoretical and educational educational theoretical information to approach the matter of psychoactive drugs in formal and nonformal education, from the perspective of the reality experienced by the participants and their life experiences.